Biological Conservation of Molluscs Based on Spatial and Temporal Distribution in Tropical Tidal Lake, Medan-Indonesia - Fredinan Yulianda; Ahmad Muhtadi; Mennofatria Boer; Majariana Krisanti; Yusli Wardiatno (Bogor Agricultural University, Indonesia, 2020)
The tidal lake ecosystem is formed by the flow of the Belmera River and seawater through a tidal process along a course of 12 km from Belawan (Malacca Strait). This lake has a tidal lake that has the characteristics of fresh water to brackish water and Mollusc communities from freshwater species to brackish water species. This study was performed to develop a mollusc conservation strategy based on the spatial and temporal distribution of Mollusca in the tides. The study was conducted from September 2018-August 2019. Mollusc samples were taken every month at high tide and low tide using a Petersen grab tool. Nine Mollusca species, consisting of three bivalves and six gastropods, were identified. Polymedosa expansa is a mollusc species that is considered for conservation. The population size of P. expansa is small, and its distribution is limited to the northern lake. P. expansa was found only in September at high tide and in December at low tide. Competition among Mollusca and habitat availability are obstacles to the survival of P. expansa. The habitat of P. expansa is mangrove, and therefore a conservation approach was carried out through improvement of mangrove quality.